The Role of Elective Neck Treatment in the Management of Sinonasal Carcinomas: A Systematic Review of the Literature and a Meta-Analysis - Galloni, Costanza (Cancers (Basel), 2021)
SIMPLE SUMMARY: The impact of elective neck treatment (ENT), whether by irradiation or dissection, on the prognosis of patients with cN0 sinonasal carcinomas remains an understudied issue. A systematic review and meta-analysis of the literature were performed according to PRISMA guidelines in order to assess regional recurrence rates after elective neck treatment compared to observation in cN0 patients. Twenty-six articles for a total of 1178 clinically N0 patients were analyzed. Overall, the 5-year overall survival was 52%; 34.6% of patients underwent elective treatment of the neck and 140 regional recurrences were registered. ENT appears to confer a lower risk of regional recurrence compared to observation alone with a cumulative OR of 0.38 (95% CI 0.25–0.58). Our meta-analysis supports the efficacy of ENT in order to reduce the risk of regional recurrence but the overall impact on survival remains uncertain. ABSTRACT: The impact of elective neck treatment (ENT), whether by irradiation or dissection, on the prognosis of patients with cN0 sinonasal carcinomas (SNCs) remains an understudied issue. METHODS: A systematic review and meta-analysis of the literature were performed according to PRISMA guidelines in order to assess regional nodal relapse rate after ENT compared to observation in cN0 SNCs patients. Twenty-six articles for a total of 1178 clinically N0 patients were analyzed. Globally, the 5-year overall survival was 52%; 34.6% of patients underwent ENT and 140 regional recurrences were registered (5.9% in the ENT cohort and 15% in the observation group). ENT appears to confer a lower risk of regional recurrence compared to observation alone, with a cumulative OR of 0.38 (95% CI 0.25–0.58). Our meta-analysis supports the efficacy of ENT for reducing the risk of regional recurrence, but its overall impact on survival remains uncertain.